Studi Etnobotani Mahoni (Swietenia mahagoni) di Desa Cowek Kecamatan Purwodadi Kabupaten Pasuruan - Hildasari, Nourma; Hayati, Ari; Zayadi, Hasan (Biota, 2021)
Mahogany (Swietenia mahagoni) is a plant that has many benefits ranging from stems, leaves, tree bark, fruit and seeds. The purpose of this study was to explore public perceptions regarding aspects of the utilization and distribution of mahogany in Cowek Village, Purwodadi District, Pasuruan Regency. The method used is descriptive exploratory which consists of: literature study, observation, interviews, data analysis using a questionnaire that has been tested for validation and reliability. Utilization among others, in the hamlet of Selowinangun, mahogany is used for 10% protection plants and 90% plant cultivation. In Krajan hamlet, mahogany is used as 20% medicine, 35% as a protective plant, 25% firewood and 20% animal feed. Then in the hamlet of Putuk as a protective plant 15% and building materials 85%. In Sumbersari hamlet, mahogany is used as 50% furniture, 40% building material, and 10% protective plant. In the Sempu hamlet itself, mahogany is used as a 50% protection plant, 25% medicine, and 25% animal feed. The most distribution of mahogany plants is in Sempu Hamlet with 13 location points, Krajan Hamlet with 10 location points, Selowinangun Hamlet with 8 location points, while in Putuk Hamlet and Sumbersari Hamlet there are 5 location points.